Lambs to the Slaughter: Leisure and Laboring-Class Poetry - Keegan, Bridget (Romanticism on the Net, 2002)
AbstractThe idea of leisure is essential to understanding how laboring-class poets conceived of themselves as writers, what they imagined the activity of poetic composition to be, and what kinds of poetic forms they felt were available to them. Further, in their poems exploring the concept of leisure, laboring-class poets illustrate an historical link between the exploitation and oppression of nature and the exploitation and oppression of the lower classes of society. It is an exploitation that is represented in poetry primarily through the suppression of leisure and the devastation of the natural or rural spaces where such leisure had occurred. This essay examines the implicit prohibition of pastoral themes for laboring-class poets from the early eighteenth to the early nineteenth centuries. Whereas early-eighteenth-century laboring-class poets depicted nature as a georgic realm, rarely representing it as the space for leisure, for early nineteenth-century poets such as Robert Bloomfield, Ann Yearsley and John Clare, the pastoral becomes the space for the poet to claim his or her rights to leisure in nature and the leisure of poetry itself. The essay argues that the expression of their protests is encoded within the generic markers of the pastoral mode, in particular through their representation of sheep and shepherds.